Trophic guilds of marine predators in the California Current Large Marine Ecosystem - Bizzarro, Joseph J.; Field, John C.; Santora, Jarrod A.; Curtis, K. Alexandra; Wells, Brian K. (Frontiers in Marine Science, 2023)
Quantifying trophic relationships of marine species is fundamental to the construction and performance of ecosystem models, development of effective ecosystem-based fisheries management strategies, and support of trait-based approaches to ecological risk assessment. Accounting for food web dynamics in taxonomically diverse ecosystems, such as the California Current Large Marine Ecosystem (CCLME), is especially challenging because of the sheer number of trophic linkages and their inherent variability. Consequently, analyses that can inform the most appropriate means of aggregating species or other taxonomic groups into assemblages or guilds are critical to reducing system complexity for modeling and management, particularly when data are limited. To provide a methodological approach that is globally applicable in such cases, we define trophic guilds within biogeographic regions of the CCLME, compare results among these regions, and discuss ecological and management implications. Within each biogeographic region, predator guilds were clearly demarcated by foraging habitat (benthic, nearshore pelagic, offshore pelagic), scale of foraging movements, and trophic position. Furthermore, trophic guilds were distinctive for each region, with species composition and the noted ecological characteristics largely driving guild structure. Such distinctions help to inform the spatial scale of ecosystem functionality and enable a definition of that scale for management